Pembelajaran Nahwu di Madrasah Hidayatul Mubtadi-ien Lirboyo Kediri - Ahmad Masrukin; Makhromi (Universitas Islam Tribakti Lirboyo Kediri, 2021)
This research is framed in a large topic of nahwu learning that specifically looks at nahwu learning practices in Madrasah Hidayatul Mubtadi-ien Lirboyo Kediri. This type of research falls into the category of field research and belongs to qualitative research. The type of research used in this study is case-studies with a non-experimental approach that is also called descriptive research. The techniques used by researchers in collecting the data are participant observations, in-depth interviews, and documentation at Madrasah Hidayatul Mubtadi-ien Lirboyo Kediri. Finally, this study managed to obtain the finding that nahwu learning became an educational priority in Lirboyo Kediri pesantren and memorization methods still dominated the learning process, even being an important evaluation to determine the success rate of learning.